Analisis Al-Wujūh Wa An-Nazā’ir Terhadap Lafaz-Lafaz Penciptaan Dalam Tafsir Al-Kasysyāf - Muhammad Rifqi Al Najib; Masruchin; Beko Hendro (MISYKAT Jurnal Ilmu-ilmu Al-Quran Hadist Syari ah dan Tarbiyah, 2026)
This study examines three Qur’anic terms of creation — khalaqa, fatara, and bada‘a — through the al-wujūh wa an-nazā’ir approach to explore their semantic variations and theological depth. The analysis reveals that khalaqa emphasizes measured and gradual creation, fatara highlights the beginning of existence, and bada‘a signifies creation without any prior example. Together, these terms illustrate Allah’s perfection and oneness as al-Khāliq, al-Fātir, and al-Badī‘. The findings affirm that the Qur’an’s lexical choices are not linguistic coincidences but deliberate expressions of divine wisdom and rhetoric. This research provides a foundation for future studies on other Qur’anic creation terms such as sana‘a and ja‘ala from both semantic and Islamic cosmological perspectives.